2001
DOI: 10.1023/a:1011181016401
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal daunorubicin in the treatment of relapsed or refractory non-Hodgkin’s lymphoma

Abstract: Liposomal daunorubicin at 100 mg/m2 every three weeks has activity in patients with relapsed or refractory NHL, including patients with prior exposure to an anthracycline. Further studies of liposomal daunorubicin in combination with other agents are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…4,5 Despite its side effects, including cardiac toxicity and bone marrow suppression, 6 the modest lipophicity and net positive charge at physiological pH made DNR an efficient substrate for P-glycoprotein (P-gp). 7,8 P-gp is known to actively pump substrates out of tumor cells through an adenosine triphosphate, resulting in multidrug resistance (MDR) and hampering the…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite its side effects, including cardiac toxicity and bone marrow suppression, 6 the modest lipophicity and net positive charge at physiological pH made DNR an efficient substrate for P-glycoprotein (P-gp). 7,8 P-gp is known to actively pump substrates out of tumor cells through an adenosine triphosphate, resulting in multidrug resistance (MDR) and hampering the…”
Section: Introductionmentioning
confidence: 99%
“…Overall, approximately a third of patients treated at doses of 100-120 mg/m 2 responded, although patients with indolent histologies were also included [16,19]. COP-X, with DaunoXome in place of doxorubicin in the CHOP regimen, has been used with encouraging response rates in two studies of patients with indolent or with relapsed or refractory NHL [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Initial clinical studies of DaunoXome focused on Kaposi sarcoma [14] while more recent studies have included patients with NHL [16][17][18][19] and various other hematological malignancies [20,21]. DaunoXome as a single agent demonstrated activity in relapsed or refractory NHL [16,19], which suggested that this agent might be used in place of doxorubicin in the CHOP regimen, with reduced toxicity and equivalent or superior efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations